جدّوجہدِ آزادی اور فتاویٰ انیسویں صدی کے فتاویٰ کا ایک تجزیاتی مطالعہ - محمد ارشد (FIKR-O NAZAR فکر ونظر, 2013)
The article attempts of analyze the fatwa literature produced as a result of British Colonial interaction with the Indian subcontinent. It focuses on the two eras. First 1803 to 1857, when the British rule had become growing reality as it extended from Delhi to Calcutta. The fatwas issued in that scenario regarded the land in question as an abode of war (Dar al-harb) and demanded Muslims to defend it by preventing the expansion of the British rule, naturally jihad in those fatwas was declared obligatory. Second post 1857 scenario, when the British established its unchallenged rule in the Indian subcontinent. Fatwas appeared in that new reality radically challenged the earlier position and insisted on adopting a compromising stance. Thus subcontinent, in these fatwas was declared as the abode of peace (Dar al-’Amn), declaring jihad was regarded as a prohibited act; moreover establishing faithful relations with the new masters was emphasized. Both of these approaches have left a great impact on Indian society as well as, on the deliberations written later. The paper attempts to provide a bird eye view on these۔